University of Baghdad - College of Education (Ibn Al-Haytham) (Journal of the College of Basic Education, 2022)
The history of our Islamic nation abounds with the likes of these outstanding people, and the interest of the early Muslims in memorizing the Qur’an, jurists, and geniuses in the sciences of philosophy, medicine, astronomy, and others, is the best evidence of interest in this segment of the nation. ), genius, precocity, brilliance, and creativity, and these terms agree on the need for the individual to reach a level of performance that exceeds his peers in a field, and this is a criterion for determining whether the individual is superior, innovative, or An innovator in the designated field